Using Cooperative Learning Model to Enhance Academic Performance of Teacher Trainees in Some Selected Topics in Integrated Science at Saint Monica’s College Of Education (International Journal of Scientific Research and Management (IJSRM), 2020)
The study sought to investigate the effects of using cooperative learning on female teacher trainees of the Colleges of Education in learning some selected topics in Integrated Science. The investigation also sought to determine whether the Cooperative Learning Approach enhances the attitude and motivation of the trainees towards learning of Integrated Science. The study was carried out at the St. Monica’s College of Education in the Mampong Municipality of the Ashanti Region. In all, 80 teacher trainees consisting of 40 each from control and experimental groups were purposively sampled to participate in the study. The teacher trainees in the experimental group were exposed to the Cooperative Learning Approach and the trainees in the control group were lectured during the period of the study. The results of the study showed that the cooperative learning strategy was very relevant and beneficial in helping the teacher trainees of the St. Monica’s College of Education to improve on their performance in, and attitudes towards, the teaching and learning of Integrated Science. It was therefore recommended among other things that the science teachers should endeavour to integrate cooperative learning into their routine methods of instruction in the teaching and learning of Integrated Science. Keywords: cooperative learning approach, purposive sampling, experimental group, college of education, motivation